Quality of life of women with gynecologic and breast cancer undergoing chemotherapy - Verônica Aparecida Ferreira; Isis do Nascimento Teixeira Silveira; Nathália Silva Gomes; Mariana Torreglosa Ruiz; Sueli Riul da Silva (Universidade Federal do Ceará, 2015)
Objective: analyzing the quality of life of women with gynecologic and breast cancer, undergoing antineoplastic chemotherapy for at least one year after treatment completion. Methods: a descriptive, cross-sectional study conducted in a University Hospital. To analyze quality of life, a sociodemographic and clinical data questionnaire and WHOQOL-bref were used. Results: 30 women with an average age of 52 years were interviewed; most were diagnosed with breast cancer and received adjuvant chemotherapy. Regarding quality of life, the most negatively affected domains were the physical and psychological domains, followed by environmental and social domains. Conclusion: including quality of life measures in clinical practice appears to be crucial in promoting comprehensive care to patients and their families.